COMBATTING SEXUAL HARASSMENT AGAINST WOMEN MIGRANT WORKERS OVERSEAS: LOOKING AT THE CONTEXTUAL FACTORS - Agus Joko Pitoyo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2016)
Violence against women is a criminal act. It involves not only in personal domain, but also within social arenas. It could be happened in social life, such as the fact of sexual harassment at work. Through qualitative retrospective cross-sectional methods, the study aimed to explore the contextual factors of sexual harassment which have occurred overseas among women migrant workers from Ponorogo, East Java, Indonesia. Several factors altogether were identi ed as logical elements contributing to the existence of sexual harassment, composed of personal factors, relationship, working environment and structural regulation. The poor mechanism of placing Indonesian workers overseas was also perceived as an exacerbating factor to the presence of the conducts. Sexual harassment was more likely happened for female migrants in young age, low skill, and poor language in host countries. Several kinds of dependencies upon employers, such as administrative dependency, social and economic dependencies, and the existence of con ict at work were identi ed as other precipitating factors to the malpractice.